1998
DOI: 10.1002/(sici)1521-3773(19981102)37:20<2754::aid-anie2754>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Polyvalent Interactions in Biological Systems: Implications for Design and Use of Multivalent Ligands and Inhibitors

Abstract: Found throughout biology, polyvalent interactions are characterized by the simultaneous binding of multiple ligands on one biological entity to multiple receptors on another (top part of the illustration) and have a number of characteristics that monovalent interactions do not (bottom). In particular, polyvalent interactions can be collectively much stronger than corresponding monovalent interactions, and they can provide the basis for mechanisms of both agonizing and antagonizing biological interactions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
1,719
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 3,819 publications
(1,757 citation statements)
references
References 151 publications
34
1,719
0
4
Order By: Relevance
“…(b) The oligovalent ligand (here, bivalent) binds a receptor of the same valency with a dissociation constant of K d,2 for the equilibrium between the fully complexed receptor and free receptor and ligand. (c) The bivalent receptor can also bind the bivalent ligand with only one receptor-ligand interaction; the complex has a dissociation constant of K d, 1 . We define the avidity (K d avidity ) as K d,2 (the equilibrium in b).…”
Section: Fig 22supporting
confidence: 53%
See 1 more Smart Citation
“…(b) The oligovalent ligand (here, bivalent) binds a receptor of the same valency with a dissociation constant of K d,2 for the equilibrium between the fully complexed receptor and free receptor and ligand. (c) The bivalent receptor can also bind the bivalent ligand with only one receptor-ligand interaction; the complex has a dissociation constant of K d, 1 . We define the avidity (K d avidity ) as K d,2 (the equilibrium in b).…”
Section: Fig 22supporting
confidence: 53%
“…There are several thorough reviews on both experimental [16][17][18] and theoretical [1,19,20] aspects of multivalency. The book by Choi is an excellent compilation of experimental results; it also discusses potential targets (e. g., receptors on pathogens, multivalent proteins, etc.)…”
mentioning
confidence: 99%
“…With the hyperbranched and tree-like structure, the dendrimers expose large portions of functional molecules at the surface. High amounts of terminal groups facilitate simultaneous interactions of the dendrimer with solvent and a variety of molecules, and therefore, the dendrimers often show high solubility and binding affinity [7]. Surface groups of the dendrimers can also be modified for different purposes, including optimized biodistribution, specific targeting and controlled release of drug molecules from the core [8].…”
Section: Introductionsupporting
confidence: 93%
“…More recently, studies revealed that multiple-contact configurations could improve the binding affinity between protein and aptamers. 81 Therefore, Goda et al developed a novel aptamerfunctionalized potentiometric biosensor with improved affinity for the target protein (Fig. 6c).…”
Section: Aptamer-based Sensing Approachesmentioning
confidence: 99%